Effects of Novel Probiotics in a Murine Model of Irritable Bowel Syndrome - Hye Gyo Chung; Yang Won Min; Chansu Lee; Sung Noh Hong; Ji Young Won; Jin Ah Jang; Cheol-Hyun Ki; Dong Kyung Chang (The Korean Journal of Gastroenterology, 2020)
Background/Aims: Dysbiosis is an important factor in the pathogenesis of irritable bowel syndrome (IBS). Several studies have reported promising results using probiotics for the treatment of IBS. This study evaluated the efficacy of novel probiotics isolated from Kimchi, a Korean fermented food, and the feces of healthy Vietnamese people in a murine model of IBS. Methods: Lactobacillus paracasei DK121 was isolated from Kimchi, and L. salivarius V4 and L. plantarum V7 were isolated from the feces of healthy Vietnamese people residing in Korea. Forty rats were allocated to receive one of the study strains, a mixture of the strains, or the vehicle. After 5 days of administration, the rats were restrained in a cage to induce IBS. The effects of the probiotics on IBS were analyzed by evaluating the stool weights and stool consistency scores. Results: The primary outcome was analyzed upon the completion of a three-week experiment. The rats in the V7 group showed lower stool weights than those in the control group at week 2 (median: 1.10 [V7] vs. 2.35 [control], p=0.04, Mann-Whitney U-test) and week 3 (median: 1.10 [V7] vs. 2.80 [control], p=0.017). The rats in the DK121 (median: 2.00, p=0.007), V7 (median: 2.00, p=0.004), and mixture (median: 1.50, p=0.001) groups showed better stool consistency scores at week 2 than the control group (median: 3.00). Conclusions: The novel probiotics have beneficial effects on defecation in a murine model of IBS. Human studies confirming the efficacy are warranted.